2013
DOI: 10.1016/j.wem.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cold Packs May Provide Insufficient Enthalpy Change for Treatment of Hyperthermia

Abstract: Experiments demonstrate that CCPs are inferior to similarly sized ice packs for thermal regulation, and lose their effectiveness more quickly. These findings support the consideration of ice packs as an alternative to chemical cold packs when cooling hyperthermic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Two pouches filled with crushed ice are positioned, one on either side of the upper part of the neck, over the jugular vein and carotid artery, creating a 'heat sink' effect in the contacting tissues (Figs 13 and 14). Although the pouches can accommodate commercially available chemical cold packs, research has shown that crushed ice has a greater cooling capacity and remains colder for longer, maximising the 'heat sink' effect (McMeekan et al 1984;Phan et al 2013).…”
Section: Use Of a Cooling Collarmentioning
confidence: 99%
“…Two pouches filled with crushed ice are positioned, one on either side of the upper part of the neck, over the jugular vein and carotid artery, creating a 'heat sink' effect in the contacting tissues (Figs 13 and 14). Although the pouches can accommodate commercially available chemical cold packs, research has shown that crushed ice has a greater cooling capacity and remains colder for longer, maximising the 'heat sink' effect (McMeekan et al 1984;Phan et al 2013).…”
Section: Use Of a Cooling Collarmentioning
confidence: 99%
“…98 Limited studies show no benefit in heat reduction with ice packs or chemical cold packs applied to these areas. 99,100 Ice packs have been found to have greater cooling capacity than chemical cold packs, 101 and if used, are most efficacious when wet and covering the entire body (to optimize conductive cooling). 99 A small translational study applied chemical cold packs to the glabrous skin of the palms, soles, and cheeks and found twice the cooling rate over traditional major vascular locations, 102 using the high-capacity blood flow of the subcutaneous arteriovenous anastomoses.…”
Section: Chemical Cold Packs/ice Packsmentioning
confidence: 99%
“…To avoid this, the temperature of the skin must remain above the temperature threshold for local vasoconstriction. The CCP of this study uses an endothermic reaction to reduce temperature and cool to approximately 13°C, 24 a temperature that is not associated with vasoconstriction, especially in the glabrous skin regions. Colder temperatures (as induced by ice packs) increase the likelihood of experiencing a vasomotor response and subsequently decreasing their local cooling effects.…”
Section: Discussionmentioning
confidence: 99%
“…The CCP were agitated, applied, and then replaced every 9 minutes, corresponding to their average cold lifespan. 24 No water was consumed during the trials, but after each trial each participant consumed the volume of water equivalent to the weight lost during the trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation